Os precedentes judiciais e a segurança jurídica no direito tributário: o caso da superação da Súmula 584 do Supremo Tribunal Federal - Cardoso, Lucas Giribone (2023)
The central theme of the research involves the study of judicial precedents and the impact they can have on legal certainty in Tax Law, based on the analysis of a concrete case from the Federal Supreme Court. With the increasingly constant action of the Judiciary in the creation of new legal rules of Tax Law, it is necessary to understand the Theory of Judicial Precedents, because, with the rise of the CPC/2015, there was a need to unify the jurisprudence, to guarantee greater clarity to the courts regarding the method of judicial decision, protecting acquired rights, good faith, and legal certainty. In a legal system in which there is no predictability, stability, and respect for the constitutional text, it is not possible to say that there is legal certainty since it is necessary to guarantee the other legal principles to have a more effective and secure legal system. In Tax Law, there are specific principles, such as legality, precedence, and nonretroactivity, which are linked to the principle of legal certainty, a fact that leads to the need for judicial decisions to observe, in a special way, judicial precedents, to guarantee greater stability in tax relations. Therefore, in this work, it will be necessary to analyze how judicial precedents can impact the preservation of these tax principles, so that there is greater protection of taxpayer rights and legal certainty. Respect for the law and the Constitution is necessary, and judicial decisions should not fail to comply with legal commands, under penalty of harming the entire Brazilian legal system and even other sectors, such as the economy. Theme 168 of the STF was chosen to exemplify to the reader how the observance of precedents is necessary so that there is greater uniformity in judicial decisions, which must observe the legal provisions and the Constitution. The principle of legal certainty is linked to the rights of citizens, such as protection of trust, protection of objective good faith and greater stability over legal rules, so that there are no contradictions between judicial decisions, thus giving greater predictability to state acts. The techniques for applying precedents, the elements of these precedents and their legal and constitutional discipline will be studied, so that later it can be understood whether the Theory of Judicial Precedents has any impact on guaranteeing legal certainty in Brazilian Tax Law, having as object of study the overcoming of precedent 584 of the Federal Supreme Court